2020
DOI: 10.1186/s40537-020-00381-y
|View full text |Cite|
|
Sign up to set email alerts
|

Cooperative co-evolution for feature selection in Big Data with random feature grouping

Abstract: A massive amount of data is generated with the evolution of modern technologies. This high-throughput data generation results in Big Data, which consist of many features (attributes). However, irrelevant features may degrade the classification performance of machine learning (ML) algorithms. Feature selection (FS) is a technique used to select a subset of relevant features that represent the dataset. Evolutionary algorithms (EAs) are widely used search strategies in this domain. A variant of EAs, called cooper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 95 publications
(139 reference statements)
0
26
0
Order By: Relevance
“…A lot of dimensionality reduction and classification approaches have been explored in literature, they are based of several measures, such as computational complexity, accuracy, among others [24]. Some of the few works done have been studies in the literature and have indicated emerging research fields such as optimization and hybridization investigations [25].…”
Section: Literature Reviewmentioning
confidence: 99%
“…A lot of dimensionality reduction and classification approaches have been explored in literature, they are based of several measures, such as computational complexity, accuracy, among others [24]. Some of the few works done have been studies in the literature and have indicated emerging research fields such as optimization and hybridization investigations [25].…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, the widely used search strategy in the FS process is EC. A taxonomy of evolutionary FS approaches [2,4,6] is illustrated in Figure 3. Evolutionary FS approaches can be categorized into three types: (1) evaluation criteria-based, (2) evolutionary computation-based, (3) the number of objectives-based.…”
Section: Feature Engineering Using Evolutionary Computationmentioning
confidence: 99%
“…The different EC algorithms that are used in the FS process are evolutionary algorithm (EA), co-evolutionary algorithm (CEA), swarm optimization, hybrid, and other algorithms. The standard algorithms in these categories are genetic algorithm (GA), genetic programming (GP), parallel GA, cooperative co-evolutionary algorithm (CCEA), particle swarm optimization (PSO), ant colony optimization (ACO), minimum redundancy maximum relevance (mRMR), teaching learning-based algorithm (TLBO), TLBO with opposition-based learning (TLBOL), conditional mutual information maximization (CMIM), binary genetic algorithm (BGA), gravitational search algorithm (GSA), artificial bee colony (ABC), memetic algorithm (MA), and differential evolution (DE) [2,4,6].…”
Section: Feature Engineering Using Evolutionary Computationmentioning
confidence: 99%
See 2 more Smart Citations